2014
DOI: 10.1128/cmr.00013-14
|View full text |Cite
|
Sign up to set email alerts
|

Human Astroviruses

Abstract: SUMMARY Human astroviruses (HAtVs) are positive-sense single-stranded RNA viruses that were discovered in 1975. Astroviruses infecting other species, particularly mammalian and avian, were identified and classified into the genera Mamastrovirus and Avastrovirus . Through next-generation sequencing, many new astroviruses infecting different species, including humans, have been described, and the Astroviridae family sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
353
3
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 342 publications
(409 citation statements)
references
References 295 publications
(433 reference statements)
21
353
3
7
Order By: Relevance
“…These observations suggest that MLB-AstVs may be more prevalent than VA-AstVs among children with diarrheal disease. All MLB-AstV strains found in this study were classified as type 2 strains, which have been found in nasopharyngeal swab and plasma samples obtained from febrile children and have been hypothesized to infect extraenteric tissues (7,50,51). Our results suggest that the prevalence of nonenteric MLB-AstVs as well as enteric viruses can be assumed by investigating wastewater samples.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…These observations suggest that MLB-AstVs may be more prevalent than VA-AstVs among children with diarrheal disease. All MLB-AstV strains found in this study were classified as type 2 strains, which have been found in nasopharyngeal swab and plasma samples obtained from febrile children and have been hypothesized to infect extraenteric tissues (7,50,51). Our results suggest that the prevalence of nonenteric MLB-AstVs as well as enteric viruses can be assumed by investigating wastewater samples.…”
Section: Discussionsupporting
confidence: 51%
“…The novel AstV strains are genetically distinct from the classic HAstV strains (20)(21)(22); in fact, VA-AstVs are genetically more closely related to mink/ovine AstVs than to classic HAstVs (20,22). To date, MLB-AstVs have been divided into 3 genotypes (MLB-AstV genotype 1 [MLB-AstV-1] to MLB-AstV-3) and VAAstVs have been divided into 4 genotypes (VA-AstV genotype 1 [VA-AstV-1] to VA-AstV-4) (7,20,23,24). It has been suggested that VA-AstV-1 and MLB-AstV-1 are associated with gastroenteritis outbreaks (23, 25), but the prevalence and etiological role of the novel AstV strains in humans remain unclear (26,27).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Astrovirus is responsible for a considerable proportion of gastroenteritis cases in young children, the elderly, and the immunosuppressed (75)(76)(77). NoV GII, which is considered to be an etiologic agent frequently associated with cases of gastroenteritis, was found in only 5% of water samples, perhaps reflecting the agricultural impact in the watershed (as reflected also in the somewhat higher level of detection of NoV GIII, at ϳ11%).…”
Section: Detection and Densities Of F-specific Coliphage And Viruses mentioning
confidence: 99%